KORUPSI KEBIJAKAN PEJABAT PUBLIK - Amalia Syauket; Rajanner P Simarmata; Cornelia Evelin Cabui (Governance, 2022)
This type of corruption has become a growing phenomenon in Indonesian society. Policy corruption was born because of the existence of certain positions with legitimate authority based on the law, but there are personal interests in the midst of the interests of the community with malicious intentions to steal state money. At this point, it is seen how the relationship between power and corrupt practices has a tendency to increase in power, the higher the potential for corruption. Qualitative research by prioritizing secondary data, focuses on seeing how the phenomenon of policy corruption is in the perspective of corruption. The results of this study indicate that the phenomenon of policy corruption related to public officials, will continue to occur considering the greedy behavior that is tucked away in every policy-making process is reinforced by weak integrity. The potential for corruption is very high in the fourth type of public policy, namely public goods policy. Because this type of public policy is a transactional mode of realization of the government's budget and that means there is a flow of money. Logically, it can be accepted that one of the epicenters of corruption is the area where there is a circulation of money that is vulnerable to corrupt behavior from state officials.